2008
DOI: 10.1080/01292980802239416
|View full text |Cite
|
Sign up to set email alerts
|

Perpetual development journalism? Balance and framing in the 2006 Singapore election coverage

Abstract: This study sought to determine if Singapore's press model has evolved beyond the development model to take on characteristics of other press models. It examined balance and framing in election coverage in the Straits Times, Singapore's dominant English newspaper, over 16 days before the 2006 Singapore General Election. As expected under the development model, and contrary to expectations under the social responsibility model, we found coverage of the competing parties lacked balance, as indicated by more cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…In Singapore, restrictive laws on outdoor demonstrations and a history of arrests of protestors have deterred outdoor protesting. Anti-government coverage in the mainstream media is limited (Cenite et al, 2008), and the White Paper protests expectedly received marginal reportage from national media. Political participation in Singapore is also very low, even among youths who consume more political content online (Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Singapore, restrictive laws on outdoor demonstrations and a history of arrests of protestors have deterred outdoor protesting. Anti-government coverage in the mainstream media is limited (Cenite et al, 2008), and the White Paper protests expectedly received marginal reportage from national media. Political participation in Singapore is also very low, even among youths who consume more political content online (Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The founding father of the nation, Lee Kuan Yew, observed that "Freedom of the news media must be subordinated to the overriding needs of Singapore, and to the primacy and purpose of an elected government" (Latif, 1998, p. 151). In 2003, the then-Information Minister echoed this, saying "The local media have an important role in our nation-building effort" (Cenite, Chong, Han, Lim, & Tan, 2008, p. 284 (Cenite et al, 2008;Wong, 2004).…”
Section: Singapore Government Media Policymentioning
confidence: 99%
“…The mainstream media views itself as the government's partner in progress and nation building, and is keenly in tune with the government's agenda (Y. S. Tan & Soh, 1994). The bias against the opposition persists right up till the 2006 election (Cenite et al, 2008), and there has been no reason to expect the Singapore Government-mainstream media relationship to change for the 2011 general election.…”
Section: Opposition Information Gap In Singaporementioning
confidence: 99%
“…Although it is a democratic republic, mainstream news in Singapore remains regulated by the ruling political party and thus strongly supports government and party's positions through greater and more positive coverage (Cenite, Chong, Han, Lim, & Tan, 2008). In 2014, Reporters Without Borders ranked Singapore 150 out of 180 on its World Press Freedom Index.…”
mentioning
confidence: 99%